Effect of Sitting Position vs. Supine Position With the Head Turned to the Affected Side on Benign Paroxysmal Positional Vertigo Fatigue - Imai, Takao; Nishiike, Suetaka; Okumura, Tomoko; Takeda, Noriaki; Sato, Takashi; Ohta, Yumi; Kamakura, Takefumi; Inohara, Hidenori (Frontiers in Neurology, 2021)
Objective: In benign paroxysmal positional vertigo (BPPV), positional nystagmus becomes generally weaker when the Dix-Hallpike test is repeated. This phenomenon is termed BPPV fatigue. We previously reported that the effect of BPPV fatigue deteriorates over time (i.e., the positional nystagmus is observed again after maintaining a sitting head position). The aim of this study was to investigate whether the effect of BPPV fatigue attenuates after maintaining a supine position with the head turned to the affected side. Methods: Twenty patients with posterior canal type BPPV were assigned to two groups. Group A received Dix-Hallpike test, were returned to the sitting position (reverse Dix-Hallpike test) with a sitting head position for 10 min, and then received a second Dix-Hallpike test. Group B received Dix-Hallpike test, were kept in the supine position with the head turned to the affected side for 10 min, and then received reverse Dix-Hallpike test followed by the second Dix-Hallpike test. The maximum slow phase eye velocity (MSPEV) of positional nystagmus induced by the first, reverse, and second Dix-Hallpike test were analyzed. Results: The ratio of MSPEV of the positional nystagmus induced by the second Dix-Hallpike test relative to the first Dix-Hallpike test was significantly smaller in group B than that in group A. There was no difference in the MSPEV of the positional nystagmus induced by the reverse Dix-Hallpike test between group A and B. Conclusions: The effect of BPPV fatigue is continued by maintaining a supine position with the head turned to the affected side, while the effect is weakened by maintaining a sitting head position. On the basis of the most widely-accepted theory of the pathophysiology of BPPV fatigue, in which the particles become dispersed along the canal during head movement in the Dix-Hallpike test, we found an inconsistency whereby the dispersed otoconial debris return to a mass during the sitting position, but do not return to a mass in the supine position with the head turned to the affected side. Future studies are required to determine the exact pathophysiology of BPPV fatigue. Classification of Evidence: 2b